Antitumor effects of combining metronomic chemotherapy with the antivascular action of ultrasound stimulated microbubbles. Issue 12 (10th January 2013) - Todorova, Margarita; Agache, Vlad; Mortazavi, Omid; Chen, Branson; Karshafian, Raffi; Hynynen, Kullervo; Man, Shan; Kerbel, Robert S.; Goertz, David E.
Abstract Considerable effort is being directed toward investigating the use of ultrasound (US) stimulated microbubbles (MB) to promote the uptake of anticancer agents in tumors. In this study we propose and investigate a new method for combining therapeutic ultrasound with anticancer agents, which is to induce antivascular effects and combine these with an antiangiogenic treatment strategy, in this case metronomic chemotherapy. This is effectively a vascular targeting rather than a drug delivery approach. Experiments were conducted on MDA‐MB‐231 breast cancer tumors implanted in athymic mice. Metronomic cyclophosphamide (MCTX) was employed as an antiangiogenic therapy and was administered through the drinking water. Ultrasound stimulated microbubble treatments (USMB) were conducted at 1 MHz employing short bursts (0.00024 duty cycle) at 1.6 MPa in combination with the commercial microbubble agent Definity. USMB treatments were performed on a weekly basis for 4 weeks and MCTX was administered for 10 weeks. The USMB induced an acute reduction of blood flow as confirmed with US contrast imaging and DiOC7 perfusion staining. Longitudinal experiments demonstrated that significant growth inhibition occurred in MCTX‐only and USMB‐only treatment groups relative to control tumors. The combined USMB and MCTX treatment group showed significant growth inhibition and survival prolongation relative to the USMB‐only (p < 0.01) and MCTX‐only treatment groups (p < 0.01). These results indicate the feasibility of a new approach to combining therapeutic ultrasound with an anticancer agent.